Dormant Flower Buds Actively Accumulate Starch over Winter in Sweet Cherry - Fadón, Erica; Herrero, María; Rodrigo, Javier (Frontiers in Plant Science, 2018)
Temperate woody perennials survive to low temperatures in winter entering a dormant stage. Dormancy is not just a survival strategy, since chilling accumulation is required for proper flowering and arbitrates species adaptation to different latitudes. In spite of the fact that chilling requirements have been known for two centuries, the biological basis behind remain elusive. Since chilling accumulation is required for the normal growth of flower buds, it is tempting to hypothesize that something might be going on at this particular stage during winter dormancy. Here we characterized flower bud development in relation to dormancy, quantifying changes in starch in the flower primordia in two sweet cherry cultivars over a cold and a mild year. Results show that, along the winter, flower buds remain at the same phenological stage with flower primordia at the very same developmental stage. But, surprisingly, important variation in the starch content of the ovary primordia cells occurs. Starch accumulated following the same pattern than chilling accumulation and reaching a maximum at chilling fulfilment. This starch subsequently vanished during ecodormancy concomitantly with ovary development before bud break. These results showed that, along the apparent inactivity during endodormancy, flower primordia were physiologically active accumulating starch, providing a biological basis to understand chilling requirements.